Influences of Weld Nugget Shape and Material Gradient on the Shear Strength of Resistance Spot‐Welded Joints - Schuster, Lilia; Olfert, Viktoria; Sherepenko, Oleksii; Fehrenbach, Clemens; Song, Shiyuan; Hein, David; Meschut, Gerson; Biro, Elliot; Münstermann, Sebastian (steel research international)
Resistance spot‐welded joints containing press‐hardened steels are seen to exhibit a fracture mode called total dome failure, where the weld nugget completely separates from one steel sheet along the weld nugget edge. The effect of weld nugget shape and material property gradients is studied based on damage mechanics modeling and experimental validation to shed light on the underlying influencing factors. For a three‐steel‐sheet spot‐welded joint combining DP600 (1.5 mm)–CR1900T (1.0 mm)–CR1900T (1.0 mm), experiments under shear loading reveal that fracture occurs in the DP600 sheet along the weld nugget edge. In subsequent numerical simulation studies with damage mechanics models whose parameters are independently calibrated for every involved material configuration, three variations of the geometrical joint configuration are considered—an approximation of the real joint, one variation with a steeper weld nugget shape, and one variation with a less pronounced gradient between weld nugget material and heat‐affected zone material properties. The results of the finite‐element simulations show that a shallower weld nugget and a more pronounced material gradient lead to a faster increase of plastic strain at the edge of the weld nugget and promote the occurrence of total dome failure.
Keywords: Materials Chemistry; Metals and Alloys; Physical and Theoretical Chemistry; Condensed Matter Physics

Cold denaturation of DNA origami nanostructures - Dornbusch, Daniel; Hanke, Marcel; Tomm, Emilia; Kielar, Charlotte; Grundmeier, Guido; Keller, Adrian; Fahmy, Karim (Chemical Communications)
The coupling of structural transitions to heat capacity changes leads to destabilization of macromolecules at both, elevated and lowered temperatures. DNA origami not only exhibit this property but also provide...
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Correction: Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koshukow, Wikentij; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koschukow, Wikentji; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Powder bed fusion of soft-magnetic iron-based alloys with high silicon content - Andreiev, Anatolii; Hoyer, Kay-Peter; Hengsbach, Florian; Haase, Michael; Tasche, Lennart; Duschik, Kristina; Schaper, Mirko (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

Quasi-In Situ Localized Corrosion of an Additively Manufactured FeCo Alloy in 5 Wt Pct NaCl Solution - Pramanik, Sudipta; Krüger, Jan Tobias; Schaper, Mirko; Hoyer, Kay-Peter (Metallurgical and Materials Transactions A)
Abstract FeCo alloys are important materials used in pumps and motors in the offshore oil and gas drilling industry. These alloys are subjected to marine environments with a high NaCl concentration, therefore, corrosion and catastrophic failure are anticipated. So, the surface dissolution of additively manufactured FeCo samples is investigated in a quasi- in situ manner, in particular, the pitting corrosion in 5.0 wt pct NaCl solution. The local dissolution of the same sample region is monitored after 24, 72, and 168 hours. Here, the formation of rectangular and circular pits of ultra-fine dimensions (less than 0.5 µ m) is observed with increasing immersion time. In addition, the formation of a corrosion-inhibiting surface layer is detected on the sample surface. Surface dissolution leads to a change in the surface structure, however, no change in grain shape or grain size is noticed. The surface topography after local dissolution is correlated to the grain orientation. Quasi- in situ analysis shows the preferential dissolution of high-angle grain boundaries (HAGBs) leading to a change in the fraction of HAGBs and low-angle grain boundaries fraction (LAGBs). For the FeCo sample, a potentiodynamic polarisation test reveals a corrosion potential (E corr ) of − 0.475 V referred to the standard hydrogen electrode (SHE) and a corrosion exchange current density (i corr ) of 0.0848 A/m 2 . Furthermore, quasi- in situ experiments showed that grains oriented along certain crystallographic directions are corroding more compared to other grains leading to a significant decrease in the local surface height. Grains with a plane normal close to the $$\langle {1}00\rangle$$ ⟨ 100 ⟩ direction reveal lower surface dissolution and higher corrosion resistance, whereas planes normal close to the $$\langle {11}0\rangle$$ ⟨ 110 ⟩ direction and the $$\langle {111}\rangle$$ ⟨ 111 ⟩ direction exhibit a higher surface dissolution.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

Auslegungsmethode zum Kleben höchstfester Stahlwerkstoffe im Landmaschinenbau - Göddecke, Johannes; Göhrs, Tim; Meschut, Gerson; Große Gehling, Manfred (Stahlbau)
Abstract In Konstruktionen des Landmaschinenbaus aus dickeren Blechen (ca. 3–10 mm) findet die Klebtechnik bislang nur wenig Anwendung, obwohl sie in anderen Einsatzgebieten bereits ein etabliertes Fügeverfahren darstellt und viele Vorteile gegenüber anderen Fügeverfahren bietet, da es bisher an Regelwerken bei der Auslegung derartiger Verbindungen fehlt. Ein wesentliches Kriterium bei der Auslegung von Verbindungen im Landmaschinenbau ist die Ermüdungsfestigkeit aufgrund der langen Nutzungsphase der Produkte und der in der Landtechnik vorherrschenden Belastungscharakteristika. Geklebte Verbindungen weisen ein hervorragendes Verhalten bei zyklischer Belastung auf. Die steigenden Anforderungen im Hinblick auf Ressourceneffizienz und Leichtbau führen zu einem Umdenken, da durch den vermehrten Einsatz höherfester Stahlwerkstoffe in Kombination mit der Klebtechnik dieses als umsetzbar erscheint. Ziel ist die Entwicklung einer Methode zur Auslegung geklebter Verbindungen in Konstruktionen mit höherfesten Stahlwerkstoffen in Anlehnung an die FKM‐Richtlinie. Die betriebsrelevanten Beanspruchungen der Landtechnik werden analysiert und an speziellen Probekörpern untersucht. Dabei werden sowohl die mechanischen, thermischen und medialen Einflussfaktoren als auch der Einfluss der Klebfugengeometrie und von Betriebslastenkollektiven untersucht. Die Erkenntnisse werden in einer KMU‐relevanten Vorgehensweise zur Ermittlung von Abminderungsfaktoren zusammengefasst, wodurch die Auslegung der Bauteilfestigkeit sowohl statisch als auch dynamisch möglich ist.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Building and Construction; Civil and Structural Engineering

Influence of hydrogel coatings on corrosion and fatigue of iron in simulated body fluid - Huang, Jingyuan; Voigt, Markus; Wackenrohr, Steffen; Ebbert, Christoph; Keller, Adrian; Maier, Hans Jürgen; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Formation of insoluble silver-phases in an iron-manganese matrix for bioresorbable implants using varying laser beam melting strategies - Krüger, Jan Tobias; Hoyer, Kay-Peter; Hengsbach, Florian; Schaper, Mirko (Journal of Materials Research and Technology)
Keywords: Metals and Alloys; Surfaces; Coatings and Films; Biomaterials; Ceramics and Composites

A comparison of heuristic, statistical, and machine learning methods for heated tool butt welding of two different materials - Gevers, Karina; Tornede, Alexander; Wever, Marcel Dominik; Schöppner, Volker; Hüllermeier, Eyke (Welding in the World)
Abstract Heated tool butt welding is a method often used for joining thermoplastics, especially when the components are made out of different materials. The quality of the connection between the components crucially depends on a suitable choice of the parameters of the welding process, such as heating time, temperature, and the precise way how the parts are then welded. Moreover, when different materials are to be joined, the parameter values need to be tailored to the specifics of the respective material. To this end, in this paper, three approaches to tailor the parameter values to optimize the quality of the connection are compared: a heuristic by Potente, statistical experimental design, and Bayesian optimization. With the suitability for practice in mind, a series of experiments are carried out with these approaches, and their capabilities of proposing well-performing parameter values are investigated. As a result, Bayesian optimization is found to yield peak performance, but the costs for optimization are substantial. In contrast, the Potente heuristic does not require any experimentation and recommends parameter values with competitive quality.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

The Influence of Heat Treatment on the Microstructure, Surface Roughness and Shear Tensile Strength of AISI 304 Clinch Joints - Zeuner, André Till; Ewenz, Lars; Kalich, Jan; Schöne, Sebastian; Füssel, Uwe; Zimmermann, Martina (Metals)
Clinching is the manufacturing process of joining two or more metal sheets under high plastic deformation by form and force closure without thermal support and auxiliary parts. Clinch connections are applicable to difficult-to-join hybrid material combinations, such as steel and aluminum. Therefore, this technology is interesting for the application of AISI 304 components, as this material is widely used as a highly formable sheet material. A characteristic feature of AISI 304 is its metastability, i.e., the face-centered cubic (fcc) γ-austenite can transform into a significantly stronger body-centered cubic (bcc) α’-martensite under plastic deformation. This work investigates the effect of heat treatment—a process that involves the formation of an oxidation layer on the sheet surface—on the forming process during joining and the resulting mechanical properties of clinch joints made from AISI 304. For this purpose, different joints made from non-heat treated and heat-treated sheets were examined using classical metallography and advanced SEM techniques, accompanied by further investigations, such as hardness and feritscope measurements. The shear tensile strength was determined, and the fracture behavior of the samples was investigated. Clear influences of heat-treatment-induced surface roughness on the joint geometry and strength were observed.
Keywords: General Materials Science; Metals and Alloys

Long-Term Behavior of Clinched Electrical Contacts - Kalich, Jan; Matzke, Marcus; Pfeiffer, Wolfgang; Schlegel, Stephan; Kornhuber, Ludwig; Füssel, Uwe (Metals)
Joining by forming operations presents powerful and complex joining techniques. Clinching is a well-known joining process for use in sheet metalworking. Currently, clinched joints are focusing on mechanically enhanced connections. Additionally, the demand for integrating electrical requirements to transmit electrical currents will be increased in the future. This integration is particularly important, for instance, in the e-mobility sector. It enables connecting battery cells with electrical joints of aluminum and copper. Systematic use of the process-specific advantages of this joining method opens up the possibility to find and create electrically optimized connections. The optimization for the transmission of electrical currents will be demonstrated for clinched joints by adapting the tool geometry and the clinched joint design. Based on a comparison of the electrical joint resistance, the limit use temperature is defined for the joining materials used based on the microstructural condition and the aging condition due to artificial aging. As a result of the investigations carried out, reliable current transmission at a constant conductor temperature of up to 120 °C can be achieved for clinched copper–copper joints. In the case of pure aluminum joints and mixed joints of aluminum and copper, long-term stable current transmission can be ensured up to a conductor temperature of 100 °C.
Keywords: General Materials Science; Metals and Alloys

Reproducibility and Scattering in Additive Manufacturing: Results from a Round Robin on PBF-LB/M AlSi10Mg Alloy - Schneider, M.; Bettge, D.; Binder, M.; Dollmeier, K.; Dreyer, Malte; Hilgenberg, K.; Klöden, B.; Schlingmann, T.; Schmidt, J. (Practical Metallography)
Abstract The round robin test investigated the reliability users can expect for AlSi10Mg additive manufactured specimens by laser powder bed fusion through examining powder quality, process parameter, microstructure defects, strength and fatigue. Besides for one outlier, expected static material properties could be found. Optical microstructure inspection was beneficial to determine true porosity and porosity types to explain the occurring scatter in properties. Fractographic analyses reveal that the fatigue crack propagation starts at the rough as-built surface for all specimens. Statistical analysis of the scatter in fatigue using statistical derived safety factors concludes that at a stress of 36.87 MPa the fatigue limit of 10 7 cycles could be reached for all specimen with a survival probability of 99.999 %.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Laser-lithographically written micron-wide superconducting nanowire single-photon detectors - Protte, Maximilian; Verma, Varun B; Höpker, Jan Philipp; Mirin, Richard P; Woo Nam, Sae; Bartley, Tim (Superconductor Science and Technology)
Abstract We demonstrate the fabrication of micron-wide tungsten silicide superconducting nanowire single-photon detectors on a silicon substrate using laser lithography. We show saturated internal detection efficiencies with wire widths ranging from 0.59 µ m to 1.43 µ m under illumination at 1550 nm. We demonstrate both straight wires, as well as meandered structures. Single-photon sensitivity is shown in devices up to 4 mm in length. Laser-lithographically written devices allow for fast and easy structuring of large areas while maintaining a saturated internal efficiency for wire widths around 1 µ m.
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Metals and Alloys; Condensed Matter Physics; Ceramics and Composites

Mn(ii) sub-nanometric site stabilization in noble, N-doped carbonaceous materials for electrochemical CO2 reduction - Kossmann, Janina; Sánchez-Manjavacas, Maria Luz Ortiz; Brandt, Jessica; Heil, Tobias; Lopez Salas, Nieves; Albero, Josep (Chemical Communications)
The reported N-doped noble carbonaceous support provides strong stabilization of Mn( ii ) sub-nanometric active sites as well as a convenient coordination environment to produce CO, HCOOH and CH 3 COOH from electrochemical CO 2 reduction.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Identification of Requirements for FE Modeling of an Adaptive Joining Technology Employing Friction-Spun Joint Connectors (FSJC) - Oesterwinter, Annika; Wischer, Christian; Homberg, Werner (Metals)
The adaptive joining process employing friction-spun joint connectors (FSJC) is a promising method for the realization of adaptable joints and thus for lightweight construction. In addition to experimental investigations, numerical studies are indispensable tools for its development. Therefore, this paper includes an analysis of boundary conditions for the spatial discretization and mesh modeling techniques, the material modeling, the contact and friction modeling, and the thermal boundary conditions for the finite element (FE) modeling of this joining process. For these investigations, two FE models corresponding to the two process steps were set up and compared with the two related processes of friction stir welding and friction drilling. Regarding the spatial discretization, the Lagrangian approach is not sufficient to represent the deformation that occurs. The Johnson-Cook model is well suited as a material model. The modeling of the contact detection and friction are important research subjects. Coulomb’s law of friction is not adequate to account for the complex friction phenomena of the adaptive joining process. The thermal boundary conditions play a decisive role in heat generation and thus in the material flow of the process. It is advisable to use temperature-dependent parameters and to investigate in detail the influence of radiation in the entire process.
Keywords: General Materials Science; Metals and Alloys

Manufacture of Defined Residual Stress Distributions in the Friction-Spinning Process: Investigations and Run-to-Run Predictive Control - Dahms, Frederik; Homberg, Werner (Metals)
Friction-spinning as an innovative incremental forming process enables high degrees of deformation in the field of tube and sheet metal forming due to self-induced heat generation in the forming area. The complex thermomechanical conditions generate non-uniform residual stress distributions. In order to specifically adjust these residual stress distributions, the influence of different process parameters on residual stress distributions in flanges formed by the friction-spinning of tubes is investigated using the design of experiments (DoE) method. The feed rate with an effect of −156 MPa/mm is the dominating control parameter for residual stress depth distribution in steel flange forming, whereas the rotation speed of the workpiece with an effect of 18 MPa/mm dominates the gradient of residual stress generation in the aluminium flange-forming process. A run-to-run predictive control system for the specific adjustment of residual stress distributions is proposed and validated. The predictive model provides an initial solution in the form of a parameter set, and the controlled feedback iteratively approaches the target value with new parameter sets recalculated on the basis of the deviation of the previous run. Residual stress measurements are carried out using the hole-drilling method and X-ray diffraction by the cosα-method.
Keywords: General Materials Science; Metals and Alloys

Optical Detection of Phase Transformations in Steels: An Innovative Method for Time-Efficient Material Characterization During Tailored Thermo-mechanical Processing of a Press Hardening Steel - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Metallurgical and Materials Transactions A)
Abstract With an innovative optical characterization method, using high-temperature digital image correlation in combination with thermal imaging, the local change in strain and change in temperature could be determined during thermo-mechanical treatment of flat steel specimens. With data obtained by this optical method, the transformation kinetics for every area of interest along the whole measuring length of a flat specimen could be analyzed by the generation of dilatation curves. The benefit of this innovative optical characterization method compared to a dilatometer test is that the experimental effort for the design of a tailored component could be strongly reduced to the investigation of only a few tailored thermo-mechanical processed specimens. Due to the implementation of a strain and/or temperature gradient within the flat specimen, less metallographic samples are prepared for hardness analysis and analysis of the microstructural composition by scanning electron microscopy to investigate the influence of different process parameters. Compared to performed dilatometer tests in this study, the optical method obtained comparable results for the transformation start and end temperatures. For the final design of a part with tailored properties, the optical method is suitable for a time-efficient material characterization. Graphical Abstract
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

Low Cycle Fatigue Performance of Additively Processed and Heat-Treated Ti-6Al-7Nb Alloy for Biomedical Applications - Hein, Maxwell; Kokalj, David; Lopes Dias, Nelson Filipe; Stangier, Dominic; Oltmanns, Hilke; Pramanik, Sudipta; Kietzmann, Manfred; Hoyer, Kay-Peter; Meißner, Jessica; Tillmann, Wolfgang; Schaper, Mirko (Metals)
In biomedical engineering, laser powder bed fusion is an advanced manufacturing technology, which enables, for example, the production of patient-customized implants with complex geometries. Ti-6Al-7Nb shows promising improvements, especially regarding biocompatibility, compared with other titanium alloys. The biocompatible features are investigated employing cytocompatibility and antibacterial examinations on Al2O3-blasted and untreated surfaces. The mechanical properties of additively manufactured Ti-6Al-7Nb are evaluated in as-built and heat-treated conditions. Recrystallization annealing (925 °C for 4 h), β annealing (1050 °C for 2 h), as well as stress relieving (600 °C for 4 h) are applied. For microstructural investigation, scanning and transmission electron microscopy are performed. The different microstructures and the mechanical properties are compared. Mechanical behavior is determined based on quasi-static tensile tests and strain-controlled low cycle fatigue tests with total strain amplitudes εA of 0.35%, 0.5%, and 0.8%. The as-built and stress-relieved conditions meet the mechanical demands for the tensile properties of the international standard ISO 5832-11. Based on the Coffin–Manson–Basquin relation, fatigue strength and ductility coefficients, as well as exponents, are determined to examine fatigue life for the different conditions. The stress-relieved condition exhibits, overall, the best properties regarding monotonic tensile and cyclic fatigue behavior.
Keywords: General Materials Science; Metals and Alloys; laser powder bed fusion; Ti-6Al-7Nb; titanium alloy; biomedical engineering; low cycle fatigue; microstructure; nanostructure

Formation of insoluble silver-phases in an iron-manganese matrix for bioresorbable implants using varying laser beam melting strategies - Krüger, Jan Tobias; Hoyer, Kay-Peter; Hengsbach, Florian; Schaper, Mirko (Journal of Materials Research and Technology)
Keywords: Metals and Alloys; Surfaces; Coatings and Films; Biomaterials; Ceramics and Composites

Formation of insoluble silver-phases in an iron-manganese matrix for bioresorbable implants using varying laser beam melting strategies - Krüger, Jan Tobias; Hoyer, Kay-Peter; Hengsbach, Florian; Schaper, Mirko (Journal of Materials Research and Technology)
Keywords: Metals and Alloys; Surfaces; Coatings and Films; Biomaterials; Ceramics and Composites

Coupled microscopic and micromagnetic depth-specific analysis of plastic deformation and phase transformation of metastable austenitic steel AISI 304L by flow forming - Rozo Vasquez, Julian; Kanagarajah, Hanigah; Arian, Bahman; Kersting, Lukas; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (Practical Metallography)
Abstract This paper presents the characterization of the microstructure evolution during flow forming of austenitic stainless steel AISI 304L. Due to plastic deformation of metastable austenitic steel, phase transformation from γ-austenite into α’-martensite occurs. This is initiated by the formation of shear bands as product of the external stresses. By means of coupled microscopic and micromagnetic investigations, a characterization of the microstructure was carried out. In particular, this study shows the distribution of the strain-induced α’-martensite and its influence on material properties like hardness at different depths. The microstructural analyses by means of electron backscattered diffraction (EBSD) technique, evidence a higher amount of α’-martensite (ca. 23 %) close to the outer specimen surface, where the plastic deformation and the direct contact with the forming tool take place. In the middle area (ca. 1.5 mm depth from the outer surface), the portion of transformed α’-martensite drops to 7 % and in the inner surface to 2 %. These results are well correlated with microhardness and micromagnetic measurements at different depths. EBSD and atomic force microscopy (AFM) were used to make a detailed characterization of the topography and degree of deformation of the shear bands. Likewise, the mechanisms of nucleation of α’-martensite were discussed. This research contributes to the development of micromagnetic sensors to monitor the evolution of properties during flow forming. This makes them more suitable for closed-loop property control, which offers possibilities for an application-oriented and more efficient production.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

The Influence of Electrode Indentation Rate on LME Formation during RSW - Böhne, Christoph; Meschut, Gerson; BIEGLER, MAX; RETHMEIER, MICHAEL (Welding Journal)
During resistance spot welding of zinc-coated advanced high-strength steels (AHSSs) for automotive production, liquid metal embrittlement (LME) cracking may occur in the event of a combination of various unfavorable influences. In this study, the interactions of different welding current levels and weld times on the tendency for LME cracking in third-generation AHSSs were investigated. LME manifested itself as high-penetration cracks around the circumference of the spot welds for welding currents closely below the expulsion limit. At the same time, the observed tendency for LME cracking showed no direct correlation with the overall heat input of the investigated welding processes. To identify a reliable indicator of the tendency for LME cracking, the local strain rate at the origin of the observed cracks was analyzed over the course of the welding process via finite element simulation. While the local strain rate showed a good correlation with the process-specific LME cracking tendency, it was difficult to interpret due to its discontinuous course. Therefore, based on the experimental measurement of electrode displacement during welding, electrode indentation velocity was proposed as a descriptive indicator for quantifying cracking tendency.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

A combinatorial study of electrochemical anion intercalation into graphite - Chugh, Manjusha; Jain, Mitisha; Wang, Gang; Nia, Ali Shaygan; Mirhosseini, Hossein; Kühne, Thomas (Materials Research Express)
Abstract Dual-ion batteries are considered to be an emerging viable energy storage technology owing to their safety, high power capability, low cost, and scalability. Intercalation of anions into a graphite positive electrode provides high operating voltage and improved energy density to such dual-ion batteries. In this work, we have performed a combinatorial study of graphite intercalation compounds considering four anions, namely hexafluorophosphate (PF <?CDATA ${}_{6}^{-}$?> 6 − ), perchlorate (ClO <?CDATA ${}_{4}^{-}$?> 4 − ), bis(fluorosulfonyl)imide (FSI − ), and bis(trifluoromethanesulfonyl)imide (TFSI − ), via first-principles calculations. The structural properties and energetics of the intercalation compounds are compared based on different sizes, geometries, and the physical and chemical properties of the intercalated anions. The staging mechanism of anion intercalation into graphite and the specific capacities, and voltage profiles of the intercalated compounds are investigated. A comparison regarding battery electrochemistry is also done with available experimental observations. Our calculated intercalation energies and voltage profiles show that the initial anion intercalation into graphite is less favorable than subsequent ones for all the anions considered in this study. Although the effect of the size of anions in a graphite cathode on various properties of the intercalated compounds is not as significant as the size of cations in a graphite anode, some distinction between the studied anions can still be made. Among the studied anions, the intercalation compounds based on PF <?CDATA ${}_{6}^{-}$?> 6 − are the most stable ones. These PF <?CDATA ${}_{6}^{-}$?> 6 − anions cause relatively small structural deformations of the graphite and have the highest oxidative ability, highest onset voltage, and highest diffusion barrier along the graphene sheets. The overall small diffusion barriers of the anions within graphite explain the high rate capability of dual-ion batteries.
Keywords: Metals and Alloys; Polymers and Plastics; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Higher MLCT lifetime of carbene iron(ii) complexes by chelate ring expansion - Reuter, Thomas; Kruse, Ayla; Schoch, Roland; Lochbrunner, Stefan; Bauer, Matthias; Heinze, Katja (Chemical Communications)
Combining strong σ-donating N-heterocyclic carbene ligands and π-accepting pyridine ligands with a high octahedricity in rigid iron(II) complexes increases the 3MLCT lifetime from 0.15 ps in the prototypical [Fe(tpy)2]2+ complex to 9.2 ps in [Fe(dpmi)2]2+12+. The tripodal CNN ligand dpmi (di(pyridine-2-yl)(3-methylimidazol-2-yl)methane) forms six-membered chelate rings with the iron(II) centre leading to close to 90° bite angles and enhanced iron-ligand orbital overlap
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Novel AgCa and AgCaLa alloys for Fe-based bioresorbable implants with adapted degradation - Krüger, Jan Tobias; Hoyer, Kay-Peter; Filor, Viviane; Pramanik, Sudipta; Kietzmann, Manfred; Meißner, Jessica; Schaper, Mirko (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Distinct photodynamics of κ-N and κ-C pseudoisomeric iron(ii) complexes - Dierks, Philipp; Kruse, Ayla; Bokareva, Olga S.; Al-Marri, Mohammed J.; Kalmbach, Jens; Baltrun, Marc; Neuba, Adam; Schoch, Roland; Hohloch, Stephan; Heinze, Katja; Seitz, Michael; Kühn, Oliver; et al. (Chemical Communications)
Two closely related FeII complexes with 2,6-bis(1-ethyl-1H-1,2,3-triazol-4yl)pyridine and 2,6-bis(1,2,3-triazol-5-ylidene)pyridine ligands are presented to gain new insights into the photophysics of bis(tridentate) iron(II) complexes. The [Fe(N^N^N)2]2+ pseudoisomer sensitizes singlet oxygen through a MC state with nanosecond lifetime after MLCT excitation, while the bis(tridentate) [Fe(C^N^C)2]2+ pseudoisomer possesses a similar 3MLCT lifetime as the tris(bidentate) [Fe(C^C)2(N^N)]2+ complexes with four mesoionic carbenes.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composite; Metallkomplexe; Optical and Magnetic Materials; Catalysis

Mechanical joining of glass fibre reinforced polymer (GFRP) through an innovative solid self-piercing rivet - Han, Daxin; Yang, Keke; Meschut, Gerson (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

Refill friction stir spot and resistance spot welding of aluminium joints with large total sheet thicknesses (III-1965-19) - Schmal, Christopher; Meschut, Gerson (Welding in the World)
Refill friction stir spot welding (RFSSW) is a highly flexible and promising solid-state joining method for aluminium alloys. Alternatively, resistance spot welding (RSW) can be stated as an appropriate joining method which can be automated and used within a high-volume production due to short process times. Both processes do not need any additional elements and a flat surface on both sides of the joints can be realised. In order to meet the modern requirements for crash safety and structural stiffness, thermal and mechanical joining methods are mainly combined by using single-component epoxy resin adhesives. Due to an insufficient knowledge about the application of both thermal joining methods for the abovementioned material combinations combined with additional adhesives, deeper investigations were done regarding the interactions of the polymers and the joining processes. Starting with a brief presentation of the boundary conditions of the investigations and the refill friction stir spot welding and resistance spot welding of high-strength aluminium alloys with sheet thicknesses bigger than 5.8 mm, the paper introduces the process-related joint properties of friction-based and resistance-based welded joints. Afterwards, the paper discusses the influences of the process parameter on the metallographic joint formation and load-bearing capacities for a selected two-sheet and four-sheet material combination. When combining the spot welding technologies with adhesives, the process parameters of the RFSSW process have to be adapted for the two-sheet combination by adding a squeeze-out step, while for RSW, just the preholding time has to be increased. Different challenges for both joining methods are shown. For RFSSW, the gap formation has to be considered when welding big total sheet thicknesses, while for RSW, the shape of the weld nugget is more important for an appropriate joint performance. Additionally, process optimisations for less adhesive incineration will be discussed for both joining processes, and the influences of the adhesive on the joint formation will be addressed with the help of load-bearing capacity evaluations. The paper closes with specific recommendations for the realisation of refill friction stir and resistance spot-welded joints with and without adhesive in the field of Al joints with big total sheet thicknesses which meet the quality demands and an outlook for further research steps will be given.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Process characteristics and influences of production-related disturbances in resistance element welding of hybrid materials with steel cover sheets and polymer core - Schmal, Christopher; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Gold(ii) in redox-switchable gold(i) catalysis - Veit, Philipp; Volkert, Carla; Förster, Christoph; Ksenofontov, Vadim; Schlicher, Steffen; Bauer, Matthias; Heinze, Katja (Chemical Communications)
Gold(ii) species catalyse the cyclisation of N(2-propyn-1-yl)benzamide to 2-phenyl-5-vinylidene-2-oxazoline without halide abstraction while the neutral gold(i) complex is inactive indicating a gold(ii/i) redox-switch.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Joining of high strength aluminum alloys by refill friction stir spot welding (III-1854-18) - Schmal, Christopher; Meschut, Gerson; Buhl, Nico (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Numerical study of polyethylene burning in counterflow: Effect of pyrolysis kinetics and composition of pyrolysis products - Karpov, A. I.; Korobeinichev, O. P.; Bolkisev, A. A.; Shaklein, A. A.; Shmakov, A. G.; Paletsky, A. A.; Gonchikzhapov, M. B. (Fire and Materials)
Keywords: Metals and Alloys; Polymers and Plastics; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials

Mimicking synaptic plasticity and learning behaviours in solution processed SnO2 memristor - Pan, Ying; Wan, Tao; Du, Haiwei; Qu, Bo; Wang, Danyang; Ha, Tae-Jun; Chu, Dewei (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Process characteristics and load-bearing capacities of joints welded with elements for the application in multi-material design - Meschut, Gerson; Schmal, Christopher; Olfermann, Thomas (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Self-locking self-pierce riveting: a new self-pierce riveting technology for multi-material applications in lightweight car body structures - Sartisson, Vadim; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Combining a high-speed mechanical joining technique with the attachment of functional elements in automotive structures - Nagel, Philipp; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Flow drill screwing of fibre-reinforced plastic-metal composites without a pilot hole - Nagel, Philipp; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Corrosion properties of bioresorbable FeMn-Ag alloys prepared by selective laser melting - Wiesener, Markus; Peters, K.; Taube, Alexander; Keller, Adrian; Hoyer, Kay-Peter; Niendorf, Thomas; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Mechanical properties of an innovative shear-clinching technology for ultra-high-strength steel and aluminium in lightweight car body structures - Hörhold, Réjane; Müller, Martin; Merklein, Marion; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Investigation on joint characteristics of laser beam welded press hardenable ultra-high strength steels with ferritic-martensitic and martensitic microstructure - Janzen, V.; Meschut, G.; Dahmen, M.; Poprawe, R.; Lindner, S.; Wagener, R.; Melz, T. (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Processing of New Materials by Additive Manufacturing: Iron-Based Alloys Containing Silver for Biomedical Applications - Niendorf, Thomas; Brenne, Florian; Hoyer, Kay-Peter; Schwarze, Dieter; Schaper, Mirko; Grothe, Richard; Wiesener, Markus; Grundmeier, Guido; Maier, Hans Jürgen (Metallurgical and Materials Transactions A)
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

Columnar molecular aggregation in the aqueous solutions of disodium cromoglycate - Agra-Kooijman, Dena M.; Singh, Gautam; Lorenz, Alexander; Collings, Peter J.; Kitzerow, Heinz-Siegfried; Kumar, Satyendra (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Planar anchoring strength and pitch measurements in achiral and chiral chromonic liquid crystals using 90-degree twist cells - McGinn, Christine K.; Laderman, Laura I.; Zimmermann, Natalie; Kitzerow, Heinz-Siegfried; Collings, Peter J. (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

The use of radiation-cured adhesives on adhesive stud assembly process - Meschut, Gerson; Süllentrop, Sebastian (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Innovative joining technologies for multi-material structures - Meschut, G.; Hahn, O.; Janzen, V.; Olfermann, T. (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Weyl asymptotics: From closed to open systems - Potzuweit, A.; Weich, Tobias; Barkhofen, Sonja; Kuhl, U.; Stöckmann, H.-J.; Zworski, M. (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Doping the nematic liquid crystal 5CB with milled BaTiO3nanoparticles - Lorenz, Alexander; Zimmermann, Natalie; Kumar, Satyendra; Evans, Dean R.; Cook, Gary; Kitzerow, Heinz-Siegfried (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Maximum hydrogen chemisorption on KL zeolite supported Pt clusters - Jensen, Christopher; Buck, Doris; Dilger, Herbert; Bauer, Matthias; Phillipp, Fritz; Roduner, Emil (Chem. Commun.)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

A zirconium methacrylate oxocluster as precursor for the low-temperature synthesis of porous zirconium(iv) dicarboxylates - Guillerm, Vincent; Gross, Silvia; Serre, Christian; Devic, Thomas; Bauer, Matthias; Férey, Gérard (Chem. Commun.)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis